Partisipasi Generasi Muda Dalam Komunikasi Politik Pada Pemilu 2024 Di Desa Medan Estate Kecamatan Percut Sei Tuan - Safitri, Ira; Sitompul, Kristina; Sembiring, Vanessa; Halking, Halking (Lembaga Dongan Dosen, 2025)
Participation of the Young Generation in Political Communication in the 2014 Election in Medan Estate Village, Percut Sei Tuan District”. The purpose of this mini research is to describe or illustrate the Participation of the Young Generation in Political Communication in the 2014 Election in Medan Estate Village, Percut Sei Tuan District. The research method in this report is quantitative qualitative research with a descriptive approach. Data collection uses observation, interviews, and documentation with data analysis techniques in the form of data reduction, data display, and data verification. The results of this study indicate that the young generation has an active role in political communication ahead of the 2024 Election in Medan Estate Village through direct communication and indirect communication using various social media to disseminate information to the wider community. The participation of the young generation is influenced by support from village officials, the desire to choose the right leader, and easy access to information through digital technology. Keywords: Young Generation, Political Communication, Election